GENOTYPE-ENVIRONMENT INTERACTION IN YIELD OF HILL COTTON GENOTYPES - Dewan, K. M.; Bhuiyan, M. S. R.; Robbani, M. G.; Sonom, M. (Bangladesh Journal of Plant Breeding and Genetics, 2017)
Stability analysis helps in understanding the adaptability of genotypes over different environmental conditions and the identification of adaptable genotypes. The experiment was conducted at the Chittagong Hill Tracts (CHT) areas of Bangladesh i.e. Bandarban, Rangamati and Khagrachari during May to September 2014 to study the genotype environment interaction effect on yield of some selected hill cotton genotypes. The experiment consisted of two factors: Factor A: Location (3 locations) - L1: Bandarban; L2: Rangamati and L3: Khagrachari; Factor B: Different cotton genotypes G1: HCG-4; G2: HCG-13, G3: HCG-15, G4: HCG-21, G5: HCG-26, G6: HCG-42, G7: HCG-51 and V8: HC-1 (Check). In case of location environment, the maximum boll per plant was recorded from Bandarban (19.13). The highest single boll weight was recorded from Bandarban (4.65 g). The highest seed cotton yield per hectare was recorded from Bandarban (1825 kg). The highest lint yield per hectare was recorded from Khagrachari (809 kg). For genotypes, maximum boll per plant (24.61), single boll weight (5.18 g), seed cotton yield per hectare (2170 kg) and lint yield per hectare (927 kg) was observed in HCG-13. In case of interaction of environments and genotypes, highest boll per plant (27.03), single ball weight (5.29 g), seed cotton yield per hectare (2170 kg), lint yield per hectare (981 kg) was observed in HCG-13 at Bandarban than the Rangamati and Khagrachari. Based on performance of eight genotypes HCG-13 followed by HCG-21 and HCG -42 was found to be highest yielder.Genotype HCG-13 was found highest yielder than the other genotypes and showed better performance at Bandarban than the Rangamati and Khagrachari.